Green Skills - Francesco Vona; Giovanni Marin; Davide Consoli; David Popp (Center for Economic Studies and ifo Institute (CESifo), 2015)
The catchword `green skills' has been common parlance in policy circles for a while, yet there is little systematic empirical research to guide public intervention for meeting the demand for skills that will be needed to operate and develop green technology. The present paper proposes a data-driven methodology to identify green skills and to gauge the ways in which the demand for these competences responds to environmental regulation. Accordingly, we find that green skills are high-level analytical and technical know-how related to the design, production, management and monitoring of technology. The empirical analysis reveals that environmental regulation triggers technological and organizational changes that increase the demand for hard technical, engineering and scientific skills. Our analysis suggests also that this is not just a compositional change in skill demand due to job losses in sectors highly exposed to trade and regulation.
Keywords: J24; Q52; 330; green skills; environmental regulation; task model; workforce composition; structural shocks